Guaranteeing real-time message deadlines in the FlexRay static segment using a on-line scheduling approach - Rodrigo Lange (2012)
In recent years, the FlexRay communication protocol been promoted as a de facto standard for in-vehicular communication. In the FlexRay protocol, the communication timeline is organized as a sequence of four segments, whereas the static segment defines a set of slots specifically designed for the transmission of synchronous messages. In this paper, we investigate the following problem: "how to allocate a minimum number of static slots to each FlexRay node, while guaranteeing that all synchronous messages will be transmitted before their deadlines." Unlike previous studies that use linear programming based techniques, we evaluate the number of allocated slots using traditional response time analysis (RTA) techniques. The use of RTA techniques allow us to consider the timing requirements imposed by the set of synchronous message streams. Unlike other approaches, the RTA-based technique proposed in this paper is able to deal with a) message stream sets where periods are not multiple of the FlexRay cycle duration, b) generation of messages at the application layer that are not synchronized with the FlexRay cycle, and c) on-line scheduling of the traffic transferred during the static segment, according to its deadline requirements. The proposed technique is integrated as a RT-Middleware in each node, to take full advantage of the proposed allocation scheme. Â© 2012 IEEE.